Establishment of Mimosa biuncifera (Fabaceae) inoculated with arbuscular mycorrhizal fungi in greenhouse and field drought conditions - Peña-Becerril, Juan Carlos (2016)
Mexico is dominated by arid or semi-arid ecosystems, predominantly characterized as xeric shrublands. These areas are frequently deteriorated due to agriculture or over-grazing by livestock (sheep and goats). The vegetation type mainly consists of thorny plant species, and among these, the dominant one in overgrazed areas is catclaw (Mimosa biuncifera). This is a nurse plant that facilitates establishment of other vegetation and promotes plant succession. Catclaw plants form a mutualistic association with arbuscular mycorrhizal fungi (AMF), which improves uptake of nutrients and water. The objective of this study was to determine the effect of inoculating catclaw plants with native AMF and starting their growth under a low water availability treatment in a greenhouse, and later transplanting them to field conditions of drought and deterioration. Field plants were evaluated according to their survivorship and growth. The seeds of catclaw plants and soil with AMF spores were collected in the Mezquital Valley of Hidalgo State, in Central Mexico. Seedlings were grown in individual pots in a greenhouse. The experimental design consisted of two levels of pot irrigation, wet (W) and dry (D), as well as the presence (M+) or absence (M-) of AMF inoculum, with 20 replicates for each treatment. The following plant parameters were recorded every week: height, number of leaves and pinnae, and mean diameter of coverage. After 20 weeks in the greenhouse, determination was made of fresh and dry biomass, relative growth rate (RGR), root/shoot ratio, real evapotranspiration (RET), water-use efficiency (WUE), and percentage of mycorrhizal colonization. The remaining plants growing under the dry treatment (M+ and M-) were then transplanted to a semi-arid locality in the Mezquital Valley. During one year, monthly records were kept of their height, number of leaves, mean diameter of coverage and survival. Results showed that compared to greenhouse plants under other treatments, those under the wet mycorrhizal (WM+) treatment were taller, had more pinnae, and were characterized by greater coverage, faster RGR, and greater fresh and dry biomass. Moreover, inoculated plants (WM+ and DM+) showed higher WUE than those uninoculated (WM- and DM-, respectively). After one year in field conditions, there was a higher survival rate for previously inoculated versus uninoculated plants. Hence, mycorrhization of M. biuncifera with native AMF inoculum increased plant efficiency in biomass production, thus favoring establishment and survival in field conditions. We concluded that inoculation of catclaw plants is recommendable for revegetation programs in deteriorated semi-arid zones.